INEC AND THE CONDUCT OF ELECTIONS IN NIGERIA: AN APPRAISAL OF THE 2007 GENERAL ELECTIONS - Odoziobodo, Severus Ifeanyi (European Scientific Journal, ESJ, 2015)
Elections are very central to the principle and practice of democracy anywhere in the world and the management of elections by any election management body is significant to the electoral process and by implication, the consolidation of democracy in any country. This paper appraises the conduct of the 2007 general elections in Nigeria conducted by the Independent National Electoral Commission (INEC). Using structural functionalism as a theoretical framework and the secondary method of data collection, the paper appraises who did what, when and how in the 2007 general elections in Nigeria, with the aim of finding out whether the election was free and fair. The finding of the research is that in conducting the 2007 general elections in Nigeria, INEC did not achieve the three imperatives of electoral governance, namely, administrative efficiency, political neutrality and public accountability and therefore, the election was not free and fair.